Interview with Ivan Martinez About the Use of Microsoft Azure in Engineering - Delgado Del Aguila, Jesús Miguel (Uptc, 2024)
In this interview, some questions were asked to Master Ivan Martinez, who is a university professor noted for his specialized knowledge in network infrastructures and his multiple participations in academic events. The questions posed to him were based on his recent study approaches, such as the use of the Microsoft Azure computing tool. In the conversation that was had with the professional, we came to understand what its usefulness is and how it can serve the user in different areas, such as work. On the other hand, the Systems Engineer concludes with the way in which his knowledge is transferred to his students with great prerogative. Finally, it is mentioned that this interview was carried out audiovisually on July 27, 2021 via Zoom, the same one that was uploaded to YouTube and was transcribed for this opportunity.